(untitled) (ASRI. Art and Society. Journal for Research in Arts and Digital Humanities, 2019)
In this article, I argue that social networks have taken on the character of an image market where the competition for attention has turned into aestheticization processes based on the use of different resources and strategies that allow the control of self-representations through the edition of the image of the Self, personal distinction through stylization, and the projection of a consistent visual identity through self-curation and transmedia narrations.